2021
DOI: 10.1016/j.celrep.2021.109599
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating the impact of age on immune checkpoint therapy biomarkers

Abstract: Highlights d We investigate the relationship of patient age and ICB therapy biomarkers d Favorable ICB biomarkers are generally more prevalent in elderly patients d The CAMA web application provides a multi-omics atlas of aging in cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 63 publications
3
36
1
Order By: Relevance
“…Further, since the TMB and age showed positive interaction, older patients had relatively higher TMB. This is consistent with a recent study showing that TMB increases with age, while the T cell receptor decreases (49). This provides unique insights into clinical prognostic diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…Further, since the TMB and age showed positive interaction, older patients had relatively higher TMB. This is consistent with a recent study showing that TMB increases with age, while the T cell receptor decreases (49). This provides unique insights into clinical prognostic diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, aging influences the inflammatory microenvironment. It was found that there is a significant increase in M2-phenotype macrophage infiltrates with increasing age in 6642 breast cancer patients [ 44 ]. With regard to low-dose ASA treatment, ASA causes the formation of anti-inflammatory lipoxins through the acetylation of COX-2 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage infiltrates account for approximately 18% of all cells in meningiomas, and their number positively correlates with the WHO grade [ 57 , 58 ]. A retrospective immunohistochemical study of 30 intracranial meningiomas by Proctor et al [ 44 ] revealed that M2 macrophages have a pro-tumoral role, and recurring or WHO grade 2 meningiomas include significantly more M2 macrophages compared to WHO grade 1 meningiomas or primary meningiomas. Conversely, M1 macrophages may act tumoricidal due to the induction of inflammatory reactions via cytotoxic cytokines and leukocyte recruitment, which potentially impede the meningioma growth [ 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“… 75-77 Targeting these pathways has been suggested as a potential strategy to prevent and treat cancer. 78 A recently published manuscript examined the correlation between age and predictive markers of ICIs response, observing increased TMB and decreased T-cell receptor diversity with aging 79 …”
Section: Characteristics Of the Older Adult Population: Finding The A...mentioning
confidence: 99%